Intersectin: The Crossroad between Vesicle Exocytosis and Endocytosis - Gubar, Olga; Morderer, Dmytro; Tsyba, Lyudmila; Croisé, Pauline; Houy, Sébastien; Ory, Stéphane; Gasman, Stephane; Rynditch, Alla (Frontiers in Endocrinology, 2013)
Intersectins (ITSNs) are a family of highly conserved proteins with orthologues from nematodes to mammals. In vertebrates, ITSNs are encoded by two genes (itsn1 and itsn2), which act as scaffolds that were initially discovered as proteins involved in endocytosis. Further investigation demonstrated that ITSN1 is also implicated in several other processes including regulated exocytosis, thereby suggesting a role for ITSN1 in the coupling between exocytosis and endocytosis in excitatory cells. Despite a high degree of conservation amongst orthologues, ITSN function is not so well preserved as they have acquired new properties during evolution. In this review, we will discuss the role of ITSN1 and its orthologues in exo- and endocytosis, in particular in neurons and neuroendocrine cells.